Method development for long-term laboratory studies evaluating contaminant assimilation processes - McSpadden, Rachael Lynne, author; Sale, Tom, advisor; Blotevogel, Jens, committee member; Butters, Greg, committee member (Colorado State University. Libraries, 2016)
Remediation technologies for soil and groundwater that are impacted by chlorinated solvents are limited when reducing contaminant concentrations below maximum contaminant levels (MCLs) established by the US Environmental Protection Agency (EPA). The limited effectiveness of current technologies is partly due to well-documented contaminant back diffusion from low-permeability (k) zones causing long-term impacts on water quality. Back diffusion out of low-k zones for extended periods of time, give strong evidence that assimilation processes are driving the fate and transport of chlorinated solvents within low-k zones. The direct impacts assimilation processes, such as sorption and degradation, have on contaminant concentrations may be slow and negligible on shorter time scales. But for longer time scales assimilation processes could have consequential effects on sites where groundwater concentrations are predicted to exceed MCLs for decades to centuries. Research studies located in the field have been carried out to study assimilation processes in low-k zones. The challenge of such field studies is capturing complete data sets from complex field environments. The challenges include inability to close the mass balance, confidently identifying assimilation mechanisms at work, and are limited to short term studies. Thus, the overall objective of this research is to advance the current knowledge of assimilative processes within low-k zones through the application of long-term (~5-10years) laboratory studies. The goal of the research presented herein, is to create a starting point for long-term laboratory studies in the hopes to quantify assimilation processes within low-k zones. Prior to conducting long-term laboratory experiments, a necessary step of establishing and testing methods need to be conducted. The research described within this thesis applies the use of short-term laboratory studies conducted over a 2 to 3 month time span to test preliminary methods, establish baseline data, and test applicability of mathematical models. The model contaminant used for the short-term laboratory experiments was tetrachloroethene (PCE). For the beginning stages of method development, the assimilation process that was isolated and focused on was sorption. Sorption was evaluated in porous media of differing properties, which included four field soils (Soil A, B, C, and D) and one lab grade soil (LGS). Two short-term column studies were tested to evaluate for viability in collecting data to be used in capturing transport and assimilation processes for use in long-term laboratory studies. The two short-term column study methods are identified throughout this document as headspace vials and ampules. The design setup for both column studies were constructed to utilize diffusive transport of contaminant with a saturated lower boundary layer of PCE, an initially clean water saturated soil column, and headspace at the upper boundary layer. For each column study design, the contaminant is transported via passive diffusion, starting from a volume of high concentration (at the lower boundary layer) to a place of low concentration (throughout the clean soil and the top of the headspace to the clean upper boundary layer). The difference between the two short-term column studies is the method of data collection. The headspace vial method allows for non-destructive sampling of the headspace over time to quantify the diffusive transport of PCE through the soil column. The ampule method utilizes a completely closed system with a destructive sampling technique where the entire ampule is extracted within methanol to help eliminate the potential for mass lost from the system due to volatilization. In addition to the two short-term column studies, batch sorption studies were conducted to gain independent measurements of sorption parameters for the four field soils used throughout the column experiments. Lastly, a numerical solution to the diffusive transport partial differential equation was developed using Mathcad™. Three sorption models are employed: linear, Freundlich and Langmuir models. The parameter values from the batch sorption study were used as inputs for the mathematical model and results were compared to the short-term column study headspace vial experiment. Results from the short-term column studies show that losses from headspace vials may limit the values of the method over time periods greater than one week, but ampules are more stable than headspace vials and show the most potential for application in long-term laboratory studies. Batch sorption studies can complement the diffusive-transport studies by allowing for resolution of sorption parameter values that are independent of transport rates. The validity of the model appears to be challenged by unaccounted losses from the headspace vials, and was therefore unable to estimate experimental data results. The results of the ampules and batch sorption studies are suggested to be used to aid in the design of the long-term studies. The laboratory experiments and modeling described herein will, in hopes, be a step closer to advance the knowledge of assimilative processes and assist in determining the assimilative capacity of low-k zones. Ultimately, this work will hopefully contribute to improved decision-making at contaminated sites, possibly allowing money spent on ineffective remedies to be directed toward more productive solutions.
Keywords: low-k zones